IMPLEMENTASI KEBIJAKAN PENGELOLAAN OBAT PADA PROGRAM JAMINAN KESEHATAN NASIONAL DI RUMAH SAKIT : LITERATUR REVIEW - Nur Diana Kholidah; Wahyu Purwanto; Yoga Nuzul Ikhsani (PARADIGM : Journal Of Multidisciplinary Research and Innovation, 2026)
The National Health Insurance (JKN) program is a strategic government instrument for realizing social justice in healthcare services. However, its effectiveness is highly dependent on drug availability and technical regulations. This study aims to evaluate the implementation of the JKN policy in improving healthcare accessibility and analyze drug governance in various healthcare facilities. The method used is a literature review with a qualitative descriptive approach to regulations and recent scientific publications. The results show that JKN significantly expands the scope of public financial protection, but faces challenges in the form of infrastructure disparities between regions. The e-catalog policy in the pharmaceutical sector has successfully reduced drug prices but poses a risk of stockouts due to distribution constraints and dependence on imported raw materials. Economically, this policy promotes supply chain efficiency and the digitization of operational planning. Synchronization of price regulations and strengthening the upstream pharmaceutical industry are needed to ensure the program's sustainability nationally.